Better Than the Euro? The European Monetary System (1979–1998). Issue 2 (4th March 2018) - Höpner, Martin; Spielau, Alexander
ABSTRACT: The euro crisis has provoked a debate on the pros and cons of adjustable exchange rate regimes that enable their participants to negotiate nominal de- and revaluations. To evaluate the functioning of such regimes, we revisit the EMU's predecessor, the European Monetary System (EMS). We show that in the EMS, devaluations did indeed help more than revaluations did hurt. Assuming that the political-economic heterogeneity of the Eurozone will not vanish in the foreseeable future, the move to a more flexible exchange rate regime might therefore be economically advantageous. However, a purely economic view ignores the huge political 'maintenance costs' of negotiable realignments, costs that the EMS members aimed at overcoming when they opted for the euro. The re-politicization of nominal exchange rate policy in today's Eurozone would therefore not end transnational political conflicts in the Eurozone but fuel new ones.